Mitochondrion-Dependent Cell Death in TDP-43 Proteinopathies - Chantal B. Lucini; Ralf J. Braun (Biomedicines, 2021)
In the last decade, pieces of evidence for TDP-43-mediated mitochondrial dysfunction in neurodegenerative diseases have accumulated. In patient samples, in vitro and in vivo models have shown mitochondrial accumulation of TDP-43, concomitantly with hallmarks of mitochondrial destabilization, such as increased production of reactive oxygen species (ROS), reduced level of oxidative phosphorylation (OXPHOS), and mitochondrial membrane permeabilization. Incidences of TDP-43-dependent cell death, which depends on mitochondrial DNA (mtDNA) content, is increased upon ageing. However, the molecular pathways behind mitochondrion-dependent cell death in TDP-43 proteinopathies remained unclear. In this review, we discuss the role of TDP-43 in mitochondria, as well as in mitochondrion-dependent cell death. This review includes the recent discovery of the TDP-43-dependent activation of the innate immunity cyclic GMP-AMP synthase/stimulator of interferon genes (cGAS/STING) pathway. Unravelling cell death mechanisms upon TDP-43 accumulation in mitochondria may open up new opportunities in TDP-43 proteinopathy research.